Hypoketotic hypoglycemia in citrin deficiency: a case report - Yoichi Wada; Natsuko Arai-Ichinoi; Atsuo Kikuchi; Osamu Sakamoto; Shigeo Kure (BMC, 2020)
Abstract Background Citrin deficiency (CD) is a recessive metabolic disease caused by biallelic pathogenic variants in SLC25A13. Although previous studies have reported ketosis in CD, it was observed at the time of euglycemia or mild hypoglycemia. Blood ketone levels concomitant with symptomatic or severe hypoglycemia in CD have not been a topic of focus despite its importance in identifying the etiology of hypoglycemia and assessing the ability of fatty acid utilization. Herein, we describe a patient with CD who had repeated episodes of hypoglycemia with insufficient ketosis. Case presentation A 1-year-old boy with repetitive hypoglycemia was referred to us to investigate its etiology. The fasting load for 13 h led to hypoketotic hypoglycemia, indicating the possibility of partial β-oxidation dysfunction. A genetic test led to the diagnosis of CD. The hypoglycemic episodes disappeared after switching to a medium-chain triglyceride-containing formula. Conclusions This case report suggests that symptomatic or severe hypoglycemia in patients with CD could be associated with relatively low levels of ketone bodies, implying that β-oxidation in these patients might possibly be partially disrupted. When encountering a patient with hypoglycemia, clinicians should check blood ketone levels and bear in mind the possibility of CD because excessive intravenous administration of glucose can cause decompensated symptoms in patients with CD as opposed to other disorders presenting with hypoketotic hypoglycemia, such as fatty acid oxidation disorders. Further studies in a large-scale cohort are warranted to confirm our speculation.